Shunt active compensation based on the Conservative Power Theory current's decomposition - Paredes, H. K M [UNESP]; Brandão, D. I. [UNESP]; Terrazas, T. M. [UNESP]; Marafão, F. P. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Considering the operation of shunt active compensators, such as active power filters, this paper proposes possible compensation strategies by means of the recent formulation of the Conservative Power Theory (CPT). The CPT current's decomposition results in several current components, which are associated with specific load characteristics (power transfer, energy storage, unbalances and/or non linearities). These current components are used for the definition of different compensation strategies, which can be selective in terms of minimizing particular disturbing effects. In order to validate the applicability of these new compensation strategies, simulation and experimental results for three-phase four-wire systems are presented. © 2011 IEEE.
Keywords: active power filters; asymmetry; conservative power theory; harmonic compensation; power factor; reactive compensation; selective compensation; Active power Filter; Harmonic compensation; Power factors; Power theory; Reactive compensation; Selective compensation; Electric power factor; Power electronics; Active filters